2019
DOI: 10.1002/ps.5487
|View full text |Cite
|
Sign up to set email alerts
|

Current understanding of the molecular players involved in resistance to rice planthoppers

Abstract: Rice planthoppers are the most widespread and destructive pest of rice. Planthopper control depends greatly on the understanding of molecular players involved in resistance to planthoppers. This paper summarizes the recent progress in the understanding of some molecular players involved in resistance to planthoppers and the mechanisms involved. Recent researches showed that host‐plant resistance is the most promising sustainable approach for controlling planthoppers. Planthopper‐resistant varieties with a host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 61 publications
(203 reference statements)
0
18
0
Order By: Relevance
“…Insects may overcome this by secreting effectors in salivary proteins or capitalizing SMs (Lu et al 2018). Although the strategies used by plants to defend against each kind of insect may vary (Harun-Or-Rashid et al 2018), common mechanisms involve JA signaling, detoxification, cell wall modifications, photosynthesis, phytohormones, and defensive SMs (for review, see Ling et al 2019;Zogli et al 2020).…”
Section: Response Of Rice To Insectsmentioning
confidence: 99%
“…Insects may overcome this by secreting effectors in salivary proteins or capitalizing SMs (Lu et al 2018). Although the strategies used by plants to defend against each kind of insect may vary (Harun-Or-Rashid et al 2018), common mechanisms involve JA signaling, detoxification, cell wall modifications, photosynthesis, phytohormones, and defensive SMs (for review, see Ling et al 2019;Zogli et al 2020).…”
Section: Response Of Rice To Insectsmentioning
confidence: 99%
“…It has been revealed that silicon (Si) amendment to plants can promote direct and indirect plant defense against piercingsucking herbivores in agriculture. 10,11 The brown planthopper Nilaparvata lugens showed long nonprobing (np) and pathway events, short-term phloem sap ingestion (N4-b), and a lower proportion of individuals with sustained phloem sap ingestion from rice plants amended with Si. 12 Similar results have been reported in the greenbug Schizaphis graminum feeding on wheat plants amended with Si, where the feeding duration and the percentage of insects that fed on phloem sap decreased owing to the fact that the stylets of S. graminum were withdrawn more often in response to Si-treated wheat plants.…”
Section: Introductionmentioning
confidence: 99%
“…Rice is a nutritious food for many phytophagous insects, and although hundreds of insects damage rice in a variety of ways, only approximately 20 major species regularly cause significant damage [ 18 ]. WBPHs are widely distributed in South Asia, Southeast Asia, and Australia, and they winter in tropical and subtropical regions.…”
Section: Discussionmentioning
confidence: 99%